Feast as Resistance - Sarah Shin (TheoLogica, 2020)
This paper takes the concept of black joy as a corporate practice of resistance against evil and extends it to apply to liturgical feasting as resistance against evil— through ritualized corporate worship (Eucharist) and table fellowship (eating a meal together). The proposal connects current discussions in analytic theology and black theology to propose an account of how the Church can help resist evil. After demonstrating how feasting in both the Eucharist and table fellowship help resist evil, the paper names two challenges to liturgical feasting and presents solutions to both problems by drawing upon the understanding of the human gaze as presented by child psychologist Vasudevi Reddy and upon theologian Eleonore Stump’s work on shame. The paper demonstrates how liturgical feasting as Eucharist and table fellowship helps to anchor and reinforce each other and provides a setting for the sharing of gazes and stories, the defeating of shame, and the forming of a collective memory that helps a community in its resistance of evil.